Pengaruh Lingkungan Kerja Dan Kepuasan Kerja Terhadap Turnover Intention Karyawan CV. Sollu Citra Muslim - Erwinda Hesti Pertiwi; Rita Tri Yusnita; Mila Karmila (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to determine the influence of the work environment and job satisfaction on turnover intention among CV employees. Sollu Citra Muslim. This research uses quantitative methods. The type of data used is primary data, with a research sample of 76 respondents from CV employees. Sollu Citra Muslim and uses the Proportional Random Sampling sampling technique. The data analysis tool used in this research is SPSS Version 25. Data collection techniques are interviews and questionnaires. The research results show that the Work Environment and Job Satisfaction simultaneously have a significant effect on Turnover Intention. The Work Environment partially has a negative and significant effect on Turnover Intention. Job Satisfaction partially has a negative and insignificant effect on Turnover Intention.Keywords: Work Environment, Job Satisfaction, Turnover Intention